Tube-ovarian abscess caused by Rothia aeria. Issue 8 (28th August 2019) - Taira, Yusuke; Aoki, Yoichi
Abstract : Rothia aeria is a gram-positive amorphous bacillus and was discovered in the Russian space station 'Mir' in 1997. It shows phylogenetic similarity to Actinomyces israelii, and as determined using 16 s ribosomal RNA gene analysis R. aeria is classified as a bacteria of the genus Actinomyces . It was found to colonise in the human oral cavity, and there are some infectious reports but none specifies gynaecological infection. A 57-year-old woman, who had been continuously using intrauterine contraceptive device, presented with fever and lower abdominal pain. She was suspected tube-ovarian abscess caused by A. israelii, but the uterine cavity culture revealed R. aeria infection. Considering surgical treatment, conservative treatment by intravenous benzylpenicillin and subsequently oral ampicillin for 6 months improved the abscess, and she has no recurrence for over 1 year.